Plan de negocios para importar material textil de Perú a Colombia por la empresa Carsh Collection para la confección y venta de ropa para mujer (2019)
Companies that are in a growth stage are always looking for a way to increase their profits through a competitive advantage, this leads many of these companies to enter international trade, this is also the case of Carsh Collection, a Colombian design company, manufacture and sale of women's clothing, whose manufacturing is located in Duitama, Boyacá. For the development of this project, the first step to define precisely the need of the Carsh Collection company, this need is to reduce the costs of the raw material without losing the quality of the brand's distinctive materials, this is how it is defined that The company needs to make imports of cheaper textile material from a country that offers such material at a lower cost, in this case, the exporting country will be Peru.